Experimental investigation on the fatigue and fracture properties of a fine pearlitic rail steel - D. Leonetti; B. Schotsman (Fracture and Structural Integrity)
This study reports an experimental investigation of the fatigue and fracture resistance of R350HT, a heat-treated pearlitic rail steel with refined microstructure used in rails. Monotonic tensile, rotating bending, linear elastic plane strain fracture toughness, and fatigue crack growth rate tests are presented. The results are used to outline the basic properties and are corroborated by fractographic investigation. This enables the identification of the dominant type of fracture. Regarding fatigue and fracture resistance, the investigated material shows similar properties as other pearlitic rail steels, such as R260. At room temperature, the dominating fracture is of brittle cleavage type, showing some ductile regions associated with pro-eutectoid.